Everyday creativity: singing goddesses in the Himalayan foothills - Narayan, Kirin (Big issues in music, 2016)
Finding form -- Tending lives through songs -- The ground that grows songs -- Attaining: the mountain daughter's many forms -- Playing: Krishna's mothers, sister, and lovers -- Going: Saili as plant and goddess -- Bathing: the transformative flows of sound -- Reaching the head